Polygamy in the Qur’an: A Thematic and Contextual Interpretation Based on Asbab al-Nuzul - Fiddaroin, Saidah (Millati: Journal of Islamic Studies and Humanities, 2025)
The study of Qur’anic verses related to polygamy has long attracted scholarly attention because polygamy is not only mentioned in religious texts but is also practiced in real life. The debate surrounding the interpretation of these verses continues, as both proponents and opponents of polygamy present their own arguments and justifications. These differing views stem from the absence of a definitive text that explicitly prohibits polygamy. The Qur’an does not present polygamy as a command or obligation. Therefore, it is important to explore these verses more deeply through the approach of asbāb al-nuzūl (the circumstances of revelation) to understand the historical context in which they were revealed. This study aims to examine Qur’anic verses on polygamy through their asbāb al-nuzūl to analyze the arguments of both proponents and opponents and to assess their relevance to contemporary life. Using a qualitative method and a literature-based approach, the author provides a descriptive analysis of verses related to polygamy. The study concludes that the Qur’an does not explicitly forbid polygamy; however, the motivations for entering polygamous marriages and their consequences must be carefully considered, just as the Prophet Muhammad (PBUH) did in his own practice.